A time to embrace same-sex relationships in religion, law, and politics - Johnson, William Stacy (Grand Rapids, Mich. : Wm. B. Eerdmans Pub. Co., 2012)
"In A Time to Embrace William Stacy Johnson brilliantly analyzes the religious, legal, and political debates about gay marriage, civil unions, and committed gay couples. This new edition includes updates that reflect the many changes in laws pertaining to civil unions/same-sex marriage since 2006"--Provided by publisher.
Introduction. Gaining perspective -- The non-affirming church -- Toward a welcoming, affirming church -- Becoming family : the consecration of same-sex love -- Freedom and equality under the law -- Toward a welcoming democracy : marriage equality in the civil polity -- Conclusion. A time to embrace.
Includes bibliographical references (p. 253-269) and indexes.
Description based on print version record.
Keywords: Same-sex marriage; Homosexuality -- Religious aspects -- Christianity; Homosexuality -- Law and legislation; Homosexuality -- Political aspects; SOCIAL SCIENCE / Sociology / Marriage & Family; Electronic books